Comércio exterior e desenvolvimento econômico do Maranhão na primeira década do século XXI: uma análise sob a ótica da competitividade revelada - SILVA, Aline Ribeiro da (2013)
The present study aims at identifying the possible connections between foreign trade and economic development. For this is done a review of the main economic theories that may explain the relationship between these two issues. The central point of analysis is to identify the extent to which trade has been the driving force of economic growth and, therefore, the development of the state. Therefore, it is necessary to conduct an analysis of the state of Maranhão export competitiveness through some indicators of foreign trade on competitiveness revealed in the period 2000-2010. Thus, it seeks to draw a diagnosis of this condition using as criteria the identification of sectors, notably, the performance indicators of the state that refers specifically to the revelation of the foreign trade sector, enabling thus substantiate the relationship between two themes. It is clear, however, that the beneficial effects provided by the external sector are limited in the state, because it lacks the infrastructure (social, economic and institutional) enough for the effects to propagate and thus achieve a higher level development although the rates of economic growth achieved it. However, it seems that something is being done in order to reverse this situation in view of the large investments that are deployed in the state.